A Criticism Of Sunbul Sinan Efendi’s Work Risālah al-Tahqīqiyya: ar-Rahs va’l-Vaks - Yunus Bozbuğa (İslam Tetkikleri Dergisi)
From the 3th/9th century until today, the concepts of samā, raqs/davrān and jahri dhikr have been central concepts in the discussions among Sufis and jurists. The Ottoman State regarded the role of the Sufis in the state’s decisionmaking mechanisms as important as of the day it was founded, and regulary conducted intellectual and political consultations with them. Until the 15th century, the Halvatī Sufis had a scientific approach to the issues mentioned by Ottoman scholars. In the 11th/17th century, during the Kadızādeliler period, this opposing attitude went as far as physical intervention. The written studies suggest that these reactions against the Sufis were carried to the dimension of social and political intervention and were exhibited by the people, the jurists, and the state. The 15th century is generally considered the period when the discussions on samā, raqs/davrān and jahri dhikr began in the Ottoman Empire. We will evaluate the beginning of these discussions and the evidence presented within the framework of the Risālah al-tahqīqiyya of Halvatī sheikh Sunbul Sinan Efendi (d. 936/1529). Sunbul Efendi is a Sufi scholar who lived during the period when the Ottoman Empire was ruled by Bayezid II (d. 918/1512), Selim I (d. 926/1520), and Suleyman I (d. 974/1566), and scientific studies were led by famous sheikhs such as Efdalzāde (d. 908/1503), Zenbilli Ali Efendi (d. 932/1526), and Kemalpaşazāde (d. 940/1534). Ibrahim al-Halabī, the imam of Fatih Mosque, was another scholar who lived at the time of Sunbul Efendi. The work of Sunbul Efendi is important for revealing the scientific discussions of samā, raqs/davrān and jahri dhikr during the 9th/15th century. Sources state that both scholars lived during the same period. Ibrahim al-Halabī has a work named ar-Rahs va’l-vaks on the mentioned concepts. This study was created on the basis of the hypothesis “ar-Rahs va’l-vaks is a rejection of Risālah al-tahqīqiyya.” As a result of the investigations made in line with the hypothesis, following the order of evidence mentioned by Sunbul Efendi on the subjects of samā, raqs/davrān and jahri dhikr, and considering the dates of the works, it is believed that ar-Rahs va’l-vaks was written as a rejection of the Risāle-i tahqīqiyya. This study is also important because it examines the concepts and subjects of the science of sufism with the methods of fiqh, handling the subject with an interdisciplinary approach.